Untargeted metabolomics in gastric and colorectal cancer patients – preliminary results - Kaźmierczak-Siedlecka, Karolina; Muszyński, Damian; Styburski, Daniel; Makarewicz, Jakub; Sobocki, Bartosz Kamil; Ulasiński, Paweł; Połom, Karol; Stachowska, Ewa; Skonieczna-Żydecka, Karolina; Kalinowski, Leszek (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Recent years, microbiota-associated aspects have been analysed in multiple disorders regarding cancers. Existing evidence pints that gut microorganisms might take part in tumour origin and therapy efficacy. Nevertheless, to date, data on fecal metabolomics in cancer patients is still strongly limited. Therefore, we aimed to analyse gut untargeted metabolome in gastrointestinal cancer patients (i.e., gastric and colorectal cancer). Patients and methods: There were 12 patients with either gastric (n=4) or colorectal cancer (n=8) enrolled and 8 analysed (n=4 each). Stool samples were collected prior to anti-cancer treatments. Untargeted metabolomics analyses were conducted by means of mass spectrometry. Results: A plethora of metabolites in cancer patients we analysed were noted, with higher homogenity in case of gastric cancer patients. We found that the level of Deoxyguanosine,m/z 266.